Natural Products Impacting DNA Methyltransferases and Histone Deacetylases - Akone, Sergi Herve; Ntie-Kang, Fidele; Stuhldreier, Fabian; Ewonkem, Monique Bassomo; Noah, Alexandre Mboene; Mouelle, Simon Eitel Misse; Müller, Rolf (Frontiers in Pharmacology, 2020)
Epigenetics refers to heritable changes in gene expression and chromatin structure without change in a DNA sequence. Several epigenetic modifications and regulators have been reported including DNA methylation, histone post-translational modifications, chromatin remodeling, and non-coding RNAs. Emerging evidence has revealed that epigenetic dysregulations are involved in a wide range of diseases including cancers. Therefore, the reversible nature of epigenetic modifications concerning activation or inhibition of enzymes involved could be promising targets and useful tools for the elucidation of cellular and biological phenomena. In this review, emphasis is laid on natural products that inhibit DNA methyltransferases and histone deacetylases making them promising candidates for the development of lead structures for anticancer-drugs targeting epigenetic modifications. We also discussed potential roadblocks associated with their use as anticancer leads.